Online brand community within the integrated marketing communication system: When chocolate becomes seductive like a person. Issue 4 (3rd July 2016) - Gabrielli, Veronica; Baghi, Ilaria
Abstract : This study proposes brand communities as an effective tool within the integrated marketing communication (IMC) system. The paper utilizes the Brand Concept Map quali-quantitative technique in order to represent and compare mental association texture within one group of non-members of a brand community versus one group of people engaged in the same community. Brand stimulus is Nutella (chocolate cream) which boasts a crowded and lively online brand community: Nutellaville. Results show that brand community is effective in terms of contribution, commonality, and complementarity within the IMC system. In particular, Nutella brand image within the online community participants is composed of some mental associations overlapping other communication tools (commonality), and by new mental associations (complementarity) referred to the brand image dimension named 'brand as person' (seductive, popular, reassuring); second, this anthropomorphism effect solves the issue of sense of guilt excited by chocolate (contribution).